The Effect of Competence, Digitalization Technology and Work Environment on Employee Productivity through Work Motivation at Jakarta Medical Center - Ratna Sari; Herry Krisnandi (International Journal of Economics Development Research (IJEDR), 2023)
The phenomenon of employee work productivity at the Jakarta Medical Center is less than optimal in carrying out the duties and functions of health services, there is a high workload and excessive demands and the limited number of health workers in dealing with the number of patients resulting in physical and mental fatigue. The purpose of the study was to analyze the effect of competence, digitalization technology and work environment on employee work productivity through work motivation at the Jakarta Medical Center. This study uses a quantitative research approach conducted using the PLS-SEM Analysis method (Partial least square path modeling-structural equation modeling analysis). Primary data collection techniques using questionnaire techniques. The study population was 150 employees with a census sample technique, all populations were sampled. Based on the discussion of the research results, it is concluded that directly there is a positive and significant effect of competence, digitalization technology and work environment on work motivation at the Medical Center. Directly there is a positive and significant effect of competence, digitalization technology, work environment, and work motivation on employee work productivity at the Jakarta Medical Center. Indirectly there is a positive and significant effect of competence, digitalization technology and work environment on employee work productivity through work motivation.